FORMAÇÃO DE PROFESSORES E EDUCAÇÃO INTERCULTURAL: CONCEPÇÕES E PRÁTICAS DE LICENCIANDOS SOBRE DIVERSIDADE CULTURAL NA EDUCAÇÃO BÁSICA (Revista Contexto & Educação, 2019)
The school often seeks to homogenize and standardize individuals with assimilationist actions, not valuing subalternized voices and denying cultural diversity. The objective of this study was to understand undergaduate students’ conceptions about cultural issues and practices in teaching at a state public school in Rio de Janeiro. The research was qualitative and semi-structured interviews were carried out with five undergraduate students in Geography, Biology and Mathematics. The interviews were analyzed with authors that deal with teacher training and practice, as well as confronting prejudice and discrimination, based on the intercultural education approach. The analysis of the reports indicated obstacles that hamper pedagogical practices, which are sometimes products of concealed and rooted prejudice in school. Even though there were different projects and debates that sought to minimize such attitudes, the analysis indicated racial and gender bias in the school, and these were naturalized by cultural daltonism in the form of "jokes". Dialogical practices were pointed as guiding methodologies of the discussions on cultural approaches. It is important to emphasize the pedagogical training that is concerned with teachers’ professional work capable of denaturing prejudice and discrimination in school.
Keywords: teacher training; elementary education; diversity; difference